(untitled) - Pinter, Charles C. (California, 1971)
Set Theory has experienced a rapid development in recent years, with major advances in forcing, inner models, large cardinals and descriptive set theory. The present book covers each of these areas, giving the reader an understanding of the ideas involved. It can be used for introductory students and is broad and deep enough to bring the reader near the boundaries of current research.
Keywords: Set theory,Lý thuyết tập hợp